Urban livestock-keeping and dengue in urban and peri-urban Hanoi, Vietnam - Jakobsen, F.; Thang Nguyen-Tien; Long Pham-Thanh; Vuong Nghia Bui; Hung Nguyen-Viet; Son Tran-Hai; Lundkvist, Å.; Anh Bui-Ngoc; Lindahl, Johanna F. (Public Library of Science, 2019)
Urban livestock provides an important source of food and income, but it may increase the risks for disease transmission. Vectors, such as mosquitoes, might increase and thereby cause an enhanced transmission of infectious diseases, such as dengue fever; considered the most important mosquito-borne viral disease globally. This cross-sectional study evaluated the awareness of dengue fever and investigated how the presence of dengue vectors is affected by the keeping of livestock in urban households in the city of Hanoi, Vietnam. From February to March 2018, during the season of lowest occurrence of dengue in Hanoi, 140 households were interviewed, of which 69 kept livestock. A general trend was observed; respondents living in the Dan Phuong district, a peri-urban district, had better knowledge and practice regarding dengue as compared to the urban Ha Dong district. In total, 3899 mosquitoes were collected and identified, of which 52 (1.33%) were Aedes species. A significant difference between the two districts was observed, with more households in Ha Dong having Aedes spp. mosquitoes (p = 0.02) and a higher incidence of dengue fever (p = 0.001). There was no significant association between livestock-rearing and the presence of Aedes spp. mosquitoes (p = 0.955), or between livestock-rearing and the incidence of dengue fever (p = 0.08). In conclusion, this study could not find any indication that households keeping livestock were at higher risk of dengue virus infections in Hanoi during the season of lowest occurrence of dengue, but clearly indicated the need of more information provided to urban inhabitants, particularly on personal protection.